PENERAPAN IPTEKS UNDANG-UNDANG NOMOR 20 TAHUN 2001 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI - Tumian Lian Daya Purba; Dahliana Kataren (JURNAL PENGABDIAN PAPUA, 2018)
Devotion this was done in the title of the application of IPTEKS the act number 20 year 2001 on corruption eradication that was done on tuesday on 11 july 2017 in the vicinity of the candidates and the member of a Party City Hanura Jayapura and on wednesday, on 12 july 2017 who held at the candidates and the member of a Party District Keerom Hanura. Activity is done due to lack of understanding about the importance of conducting corruption eradication for candidates and party members in the neighborhood hanura party because of the ignorance the council of representatives and prospective members of representatives particularly dilingkungan hanura party leadership council branches and the city of jayapura leadership council district branch keerom have understanding for better and can take the lesson from from cases of corruption that has happened and can do prevention at a later date so that corruption not continue to grow and become culture particularly in papua province. Output from devotion this is steps and for better understanding is good about the law no.20 in 2011 on corruption eradication for the and members of representatives especially in hanura party leader council Jayapura the city and the board head branch of Keerom District. Keywords : Crimes, Corruption, Eradication